Character Design For Educational Board Game “Kreasi Bento Bersama Teman Sehat” To Prevent Picky Eater Behavior In Preschool Children - Anwar, Putri Anindita; Aji, Restu Ismoyo; Yani, Aditya Rahman (Universitas Ciputra, 2025)
Preschool children often display picky eating behavior due to their growth stage and independence in choosing food, which can lead to unbalanced nutrition. This research focuses on developing character designs for an educational board game that introduces various nutritious foods in an engaging way. Using a qualitative method, primary data were collected through Focus Group Discussions (FGD), interviews, and observation, while secondary data came from literature studies. The data were analyzed descriptively to identify behavioral and visual patterns suitable for early childhood audiences. The analysis produced the concept “Active and Independent Behavior” as the foundation for character design. The resulting visual outcomes include five characters: four main figures called Teman Sehat and one antagonist, Monster Manis si Tetangga Menyebalkan. Each character was designed in an anthropomorphic style using simple shapes and bright colors to emphasize friendliness and emotional connection. The findings are expected to inform future design practices for educational media that promote healthy eating habits through visual storytelling and interactive play.